Gender and social equity in primary education : hierarchies of access - Ramachandran, Vimala (Sage Publications, 2004)
This book highlights the complexities of gender and social equity in primary education in India. It makes an assessment of the District Primary Education Programme and supplements this with six qualitative micro-studies from different states for a more extensive analysis.